Information management in the smart city. Issue 3 (1st October 2018) - Stone, Merlin; Knapper, Jonathan; Evans, Geraint; Aravopoulou, Eleni
Abstract : Purpose: The purpose of this paper is to investigate information management in a smart city. It identifies the main trends in progress and how innovation in information technology is helping all those in the smart city ecosystem in terms of generating new sources of data and connecting them. It investigates how information management in the smart city may go through several phases, but contests the notion that the co-ordinated information management that is the dream of many city managers is an appropriate vision, given the tendency in the private sector for competing information platforms to develop, giving value in different ways. Design/methodology/approach: This paper has been written by using a combination of academic insight and literature, extensive research of relevant grey literature (e.g. blogs and industry press) and interviews and interaction with some of the organisations involved in developing and implementing the smart city concept, including public transport organisations, other data providers, analysts and systems and sensor suppliers. Findings: Smart city concepts are evolving in different ways, with divergence of views which involves centralisation and control of information by city authorities and a more democratic view in which the information is managed on different platforms between which smart city stakeholders can choose. Research limitations/implications: The research method is exploratory. Validating the findings would require a more structured approach in which stakeholders of all kinds are consulted. Practical implications: All organisational stakeholders in the idea and delivery of smart cities need to consider how their interests in smart city information and those of other stakeholders are evolving and to what extent they should be in partnership with other members of the ecosystem in generating and using the information. Social implications: Individuals, whether workers, commuters, shoppers, tourists or others, will be greatly affected by the evolution of smart city information, and their choices about whether to be smart themselves will have an important effect on the benefits they receive from city smartening and on the viability of the smart cities. Originality/value: Little research has been carried out into the different choices organisations and individuals have in terms of how they will relate to smart city information and how they can manage it. This research makes a start on this task.